The combined diversification breadth and mode dimensions and the performance of large diversified firms - Simmonds, Paul (Strategic Management Journal, 1990)
This paper examines the impact of the symbiotic relationship between diversification breadth and mode on firm performance. Seventy‐three Fortune 500 firms were classified by diversification breadth (related/unrelated) and mode (internal/external) and their performance during the period 1975–84 analyzed on four financial performance measures. The two related categories (related‐internal/related‐external) were generally higher performers than the two unrelated categories (unrelated‐internal/unrelated‐external) as hypothesized, but the differences were not significant on most performance measures. The unrelated‐external category appears to be the worst performer, which presents a dilema since this strategy has dominated the conglomerate movement.